SIMULASI MESIN HIERARCHICAL MULTI- STATES (HMS) UNTUK SPESIFIKASI SISTEM WAKTU-NYATA - Mukhlash, Imam
ABSTRACT: In this thesis, we study a method for specification modelling of real-time systems which uses multi-level specification with Hierarchical Multi-States machine (HMS machine). A software prototype, which is called SIM-HMS, has been developed for simulating the model. HMS machines are high level automata, in which multiple states can be active at any time, multiple transitions can be fired simultaneously, and states can be decomposed hierarchically into lower level machine. Logical and temporal dependencies among states and transitions can be represented by a formal description. The specification modelling of real-time systems using multi-level HMS machines is carried out as follows. Specifications are expressed in terms of non-deterministic abstract machines that represent the generic behaviour of the entire system and requirements are expressed as higher level abstract machines that define the desirable bahaviours of the non-deterministic lower level machines. This implies that each higher Ievel specification imposes some constraints on the lower level specifications. The Coad-Yourdon object-oriented method is used as the analysis and design method. SIM-HMS prototype has been implemented in Borland Delphi 2.0. Object-oriented testing proposed by Pressman is used as the software testing method.